FAKTOR-FAKTOR YANG MEMPENGARUHI SENJANGAN ANGGARAN DI SKPD KABUPATEN KARANGASEM BALI - Puspitha, Desak Made Ayu Pradnya; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The aims of this research for getting empirical evidence of the factors affecting budgetary slack in SKPD Karangasem Bali. Population of this research is all of the SKPD in Karangasem, Bali District that consist of 40 SKPD. The sample that used in this research, it determine by using  saturation sampling method and took 40 samples. The respondent of this research is the head of SKPD, head of financial sub-division, Head of programming sub-division, evaluation, and reporting of each SKPD, so that the total of number the respondents as much as 120 respondent. The data collection method that used is survey method with questioner instrument. The result of this research questioner counted by using likert scale.The technique data analysis that used multiple linear regression analysis. The result of this research show that participation budget, asymmetry information, budget emphasis, and task complexity, have positive and significant impact on budgetary slack whereas organizational commitment, and clarity of budget targets have negative and significant impact on budgetary slack. Keywords : budget, budget slack, SKPD